Protección Social, Instrumento Jurídico-Político de Efectividad del Estado Social de Derecho. (2021)
eng:Colombia is established as a Social State of Law, manager and guarantor of fundamental principles, embracing specific interventionist models in democracy and social rights; The doctrine regarding this topic is lavish and enriched, indicating a series of parameters that cover contingencies and eventualities. The population in all its stages needs the state to be vigilant and protective, eliminating all possible discrimination, treating them equally and equally. Social protection seeks to create actions and institutions to develop sustainability for people who are at risk so that they can access services that improve their living conditions through programs, strategies, policies, projects and development plans. Manage contingencies that arise, such as social security and financial protection, so that higher quality of services are maintained and achieved, achieving effective coverage for all social sectors; These organizations are created to positively give people solutions and aids such as health, occupational risks, pensions and complementary social services in a timely manner. Guardianship as a protection mechanism is filed by citizens for the deficiencies that affect the system, however, we can notice an advance in the sources of law in trying to resolve contingencies that arise in people and communities. It should be clarified that these institutions are not charitable if it is not a duty of the state for its inhabitants, those who manage these aids are in favor of people and family members more in political interests.